(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the preemptive analgesic effect of amantadine on postoperative pain control in female dogs that underwent ovariohysterectomy. Twenty female dog were randomly assigned to two groups of ten. The control group (CONTROL) received oral placebo capsules, while the amantadine (AMANT) group received 5 mg/kg of oral amantadine one hour before sedation. All the animals were premedicated with 3 mg/kg (IM) meperidine, induced with propofol and maintained with isofluorane. The transanesthetic physiological parameters were recorded, and postoperative pain was evaluated every hour after extubation for six hours with the Dynamic Interactive Visual Analog Scale (DIVAS) and mechanical nociceptive threshold (MNT) and when the necessary analgesic rescue was administered (morphine, 0.2 mg/kg (IM)). During the surgical procedure, there was no significant difference in the variables measured between the two groups. Regarding postoperative pain assessment, there was a significant difference in the DIVAS score (p = 0.004) between the groups, in which AMANT required fewer rescues than did CONTROL (p = 0.03). The MNT was significantly higher ​​in AMANT than in CONTROL (p = 0.03). The results suggested that the preoperative administration of amantadine decreased analgesic requirement in female dogs that underwent elective ovariohysterectomy.